JA:2021-23. Ideal Tracking and Analytics: Incorporating Modern Toolsets to Enhance Analysis of User Acquisition and Behavior on AgInjuryNews.org. Issue 3 (2nd July 2020) - Pilz, Matthew; Burke, Rick; Redmond, Emily; Sauer, Megan; Weichelt, Bryan
ABSTRACT: Purpose : Enhanced monitoring of user acquisition and online use patterns throughout the AgInjuryNews.org data repository is imperative toward understanding overall website usage, trends, and behavior. This study examines how implementing refined, modernized analytical toolsets can provide more granular and versatile tracking of data and, in turn, reveal new focus areas to maximize effectiveness of data dissemination to end users. Methods : Collection of analytical data was expanded from its original rudimentary form to include advanced capabilities of Google Tag Manager (GTM), beginning October 18, 2019. This solution allows real-time, adaptable tracking of all operations and actions across the website. GTM also provides enhanced tie-ins with social media referrals and advertising campaign events. By using GTM as the new baseline analytics foundation, it becomes possible for ad-hoc integration of over 50 third-party analytical components and services. Results/Findings : The post-GTM dataset has not yet matured; more time and website traffic is needed to develop a comprehensive picture of overall usage behavior to optimize the content and user experience. Preliminary analysis has led to the discovery of common user actions including specialized filtering of injury data by age group and number of victims, as well as common search queries including "Tractor" and "Silo." We have also observed retention deficits by users who arrive initially through social media campaigns versus organic return-visitor traffic. Practical application : Evaluating the GTM-based analytical dataset of AgInjuryNews.org allows for a deeper understanding of trends and behaviors relating to agricultural injury research. The findings help determine strengths and weaknesses in our existing web interface so refinements can be made to improve user retention and website functionality. For instance, by studying commonly searched topics and filter options we can better target social media ads and encourage more organic return-visitor traffic. This knowledge allows us to refine future campaigns and tailor first-time visitor experiences to better engage and retain our prospective audience.